SYMBOLIC INTERACTIONISM BETWEEN BANK EMPLOYEES (STUDY OF FINANCE STAFF OF BANK SYARIAH INDONESIA KCP BONDOWOSO) - Avita Nurfianti Asrori (IJED: International Journal of Economy Development Research, 2024)
This research aims to find out about the form of interaction used between employees of Bank Syariah Indonesia KCP Bondowoso in increasing work effectiveness and analyze George Herbert Mead's theory of symbolic interaction on the relationship between employees at Bank Syariah Indonesia KCP Bondowoso. This research is important to be conducted in order to help in designing better financial management strategies to increase employee productivity and cooperation in the work environment. This study uses a qualitative descriptive method of phenomenology. In accordance with the focus studied in the study, the data mining process is carried out by means of a descriptive qualitative approach, data collection techniques in the research using several stages, namely observation, interviews, and documentation then analyzed using descriptive qualitative. To achieve this goal, the researcher uses George Herbert Mead's symbolic interaction theory which has 3 concepts, namely mind, self, and society, it can be found that the importance of relationships between employees in improving the quality of work and the atmosphere in the work environment. From the results of the above research, it can be concluded that the form of interaction used by Bank Syariah Indonesia KCP Bondowoso employees in the work environment is interpersonal communication, where the interaction applies several forms of interaction, namely with openness, empathy, support, a sense of positivity, and equality among colleagues which can improve harmonious relationships, inclusive work culture, and effective bank employee performance.